(untitled) (Scientific journal of the Fergana State University, 2025)
This study focuses on improving the health of children and adolescents in the field of physical education and addressing the issues of treating respiratory organ diseases through physical activities. The analysis of specialized literature from our country and abroad indicates the necessity of conducting scientific-pedagogical research to solve problems related to respiratory organ diseases. Foreign scholars emphasize the increasing need for practical knowledge and skills in treating students with respiratory organ diseases. The research analyzes physiological processes such as the amount of oxygen consumed by muscles during physical labor, mechanisms for enhancing the functions of the respiratory and circulatory systems, as well as changes in lung ventilation and increases in heart rate. As a result, the effectiveness of the circulatory and respiratory systems improves during physical activity, leading to better oxygen supply to the muscles. This study highlights the importance of physical education in maintaining and developing the health of children and adolescents.